Anxiety and Attitudes of Elementary School Children after Facing Covid-19 Pandemic - Anggriani, Rastry; Irwansyah; Majid, Bahri (Bantayang Omni Cendekia, 2024)
Background: Covid-19 is a pandemic detected at the end of 2019 that causes people of all ages feeling anxious, including school-age children. This anxiety may cause changes in children's attitudes and behaviors to maintain health after the Covid-19 pandemic. The pandemic that has hit all parts of the world, both developed and developing countries, has not entirely ended. The impact of the Covid-19 pandemic has become a concern for everyone, including school-age children, as it may cause anxiety. Anxiety that occurs continuously can cause stress to depression. Objective: This study aimed to determine the relationship between anxiety and the attitude of elementary school children after facing the Covid-19 pandemic. Methods: This study utilized descriptive correlation with a cross-sectional study approach. The study employed total sampling techniques, which included school-age children accounted for 70 respondents. Results: Of 70 respondents, 11 respondents (15.7%) experienced anxiety, while 59 people (84.3%) were not anxious. Of those respondents, 7 respondents (10.0%) had a negative attitude, while the remaining 63 respondents (90.0%) had a positive attitude. Respondents with no anxiety and negative attitudes amounted to 7 people (11.9%), while those who were not anxious and had a positive attitude amounted to 52 people (88.1%). The Chi- square test with the alternative Fisher Exact test resulted in a p-value= 0.285. This means that there is no relationship between anxiety and the attitude of elementary school children after facing the Covid-19 pandemic. Conclusion: Anxiety has no correlation with attitude in elementary school children after facing Covid-9 pandemic.